Learning computer programming: Implementing a fractal in a Turing Machine - Pereira, Hernane B. de B.; Zebende, Gilney F.; Moret, Marcelo A. (Computers and education, 2010)
It is common to start a course on computer programming logic by teaching the algorithm concept from the point of view of natural languages, but in a schematic way. In this sense we note that the students have difficulties in understanding and implementation of the problems proposed by the teacher. The main idea of this paper is to show that the logical reasoning of computer programming students can be efficiently developed by using at the same time Turing Machine, cellular automata (Wolfram rule) and fractals theory via Problem-Based Learning (PBL). The results indicate that this approach is useful, but the teacher needs introducing, in an interdisciplinary context, the simple theory of cellular automata and the fractals before the problem implementation.